Surface processing of silicon-based materials: silicon, silicon oxide and PDMS - Pozov, Sergey (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2016)
Recent advances in nanotechnology have generated new forefronts in materials science and engineering. Surface modification at micro- and nano-scale leads to a wide range of surface characteristics such as roughness, hydrophobicity/hydrophilicity, surface charge/energy, biocompatibility and reactivity. Motivated by the wide range of applications, this work investigates two of the main processes for nanoscale surface modification: Thermal Oxidation and Non-Reactive Plasma Processing. An experimental approach is employed in this thesis where systematic synthesis/processing‒structure‒properties‒performance is undertaken in a controlled manner until structure‒property relations are established that will form the scientific basis for surface optimization for specific applications: surface tailoring. In Part A of the thesis, thermal growth of SiO2 thin films is investigated in order to understand the physics of thermal oxidation of Silicon and the characteristics of the resulting products. SiO2 thin films were thermally grown and tested for their resulting thicknesses (WLRS), densities (XRR), topography (AFM), and reflectivity (UV/VIS Spectroscopy). It is shown that amorphous-SiO2 thin films with oxidation rates of ~40 nm/hour are produced. The experimentally obtained thicknesses showed excellent correlation with theoretical predictions calculated by the Deal–Grove model. The color of the grown surfaces depends on the thickness of the layer, which through a color map gives quick optical access to film thickness. In Part B of the thesis, the effects of a non-reactive inductively coupled plasma (ICP) processing (Argon Ion Bombardment) on Si, SiO2 and PDMS are studied. The physical, topographical, optical and wetting characteristics of the processed surfaces revealed that in the case of hard materials, uniform and high quality etching rates of 0.1–1.5 nm/min were achieved. On the contrary, PDMS plasma exposure led to impressive surface wrinkles that can be attributed to a stiff layer generation that tends to buckle with specific wavelengths that strongly depend on ion energy and specific amplitudes that depend on both ion energy and fluence. Additionally, wetting characteristics of plasma exposed PDMS surfaces showed a significant reduction in CA linked to the removal of methyl groups from the exposed surface and increase of polar functionalities. However, the hydrophobic nature was recovered in time, due to the migration of low molecular weight polar groups from the surface to the bulk of the material. The transmittance spectra of the PDMS surfaces remained almost unchanged whereas there was a reduction on normal reflectance attributed to an increase in diffusive scattering caused by surface patterning.
Keywords: Nanotechnology; Silicon